Acute Lower Respiratory Infections Associated With Respiratory Syncytial Virus in Children With Underlying Congenital Heart Disease: Systematic Review and Meta-analysis. (10th October 2019) - Chaw, Pa Saidou; Wong, Stephanie Wen Lan; Cunningham, Steve; Campbell, Harry; Mikolajczyk, Rafael; Nair, Harish; ,
Abstract: Background: Respiratory syncytial virus (RSV) is the most common viral pathogen associated with acute lower respiratory infections (ALRIs), with significant childhood morbidity and mortality worldwide. Estimates reporting RSV-associated ALRI (RSV-ALRI) severity in children with congenital heart disease (CHD) are lacking, thus warranting the need to summarize the available data. We identified relevant studies to summarize the findings and conducted a meta-analysis of available data on RSV-associated ALRI hospitalizations in children aged <5 years, comparing those with underlying CHD to those without CHD. Methods: We conducted a systematic search of existing relevant literature and identified studies reporting hospitalization of children aged <5 years with RSV-ALRI with underlying or no CHD. We summarized the data and conducted (where possible) a random-effects meta-analysis to compare the 2 groups. Results: We included 18 studies that met our strict eligibility criteria. The risk of severe RSV-ALRI (odds ratio, 2.2; 95% confidence interval [CI], 1.6–2.8), the rate of hospitalization (incidence rate ratio, 2.8; 95% CI, 1.9–4.1), and the case-fatality ratio (risk ratio [RR], 16.5; 95% CI, 13.7–19.8) associated with RSV-ALRI was higher among children with underlying CHD as compared to those without no CHD. The risk of admission to the intensive care unit (RR, 3.9; 95% CI, 3.4–4.5), need for supplemental oxygen therapy (RR, 3.4; 95% CI, .5–21.1), and need for mechanical ventilation (RR, 4.1; 95% CI, 2.1–8.0) was also higher among children with underlying CHD. Conclusion: This is the most detailed review to show more-severe RSV-ALRI among children aged <5 years with underlying CHD, especially hemodynamically significant underlying CHD, as compared those without CHD, supporting a need for improved RSV prophylactics and treatments that also have efficacy in children older than 1 year.